Electronically Reconfigurable Photonic Switches Incorporating Plasmonic Structures and Phase Change Materials (Adv. Sci. 20/2022). Issue 20 (15th July 2022) - Farmakidis, Nikolaos; Youngblood, Nathan; Lee, June Sang; Feldmann, Johannes; Lodi, Alessandro; Li, Xuan; Aggarwal, Samarth; Zhou, Wen; Bogani, Lapo; Pernice, Wolfram HP; Wright, C David; Bhaskaran, Harish
Abstract : Integrated Opto‐Electronics In‐memory computing mimics biological neurons by collocating the memory and processing unit. In article number 2200383, Harish Bhaskaran and co‐workers engineer a path to perform data‐storage and computations by electronically modulating the intensity of light. By defining plasmonic structures to confine optical power to a nanoscale volume and by employing active phase‐change materials, the authors demonstrate ultra‐low energy, non‐volatile switching with electrical and optical readout.